Quantification of Unimolecular Photoreaction Kinetics: Determination of Quantum Yields and Development of Actinometers—The Photodegradation Case of Cardiovascular Drug Nisoldipine - Mounir Maafi; Wassila Maafi (International Journal of Photoenergy)
The lack of integrated rate-laws for photoreactions has led to carry out the treatment of drugs photodegradation kinetic data using the classical zeroth-, first-, and second-order kinetics that were originally developed for thermal reactions. The recent developments of Φ-order kinetic models has opened new perspectives in the treatment of photoreaction kinetics of systems involving a photolabile molecule (A) transforming into a photochemically and thermally stable product (B), that is, the AB(1Φ) photoreaction systems. Within this framework, the kinetics of cardiovascular and photosensitive drug nisoldipine (NIS) has been rationalised. Continuous and monochromatic irradiation of NIS in ethanol obeyed Φ-order kinetics with a sigmoid-shaped quantum yield variation with irradiation wavelength (0.0041–0.35 within 235–390 nm spectral region). Both NIS initial concentration-induced self-photostabilisation effect and the photostabilisation by absorption competitors were quantified (up 70%) and related to a reduction of the photokinetic factor. Finally, the Φ-order kinetics also served to demonstrate the actinometric potential of NIS for the 320–400 nm dynamic range.